GE_GERICHTE A/959/2024 vom 25. November 2024 - GE Cour de justice (2024)
DROIT D'HABITATION;REVENU DE LA FORTUNE IMMOBILIÈRE(DROIT FISCAL);USUFRUIT | lifd.21.al1.letb; LPFisc.24.al1.letb; LIPP.48; LCP.76.al5